The course of subjective sleep quality in middle and old adulthood and its relation to physical health - Sakari Lemola; David Richter (Deutsches Institut für Wirtschaftsforschung (DIW), 2012)
Objective: Older adults more often complain about sleep disturbances compared to younger adults. However, it is not clear whether there is still a decline of sleep quality after age 60 and whether changes in sleep quality in old age are mere reflections of impaired physical health or whether they represent a normative age dependent development. Method: Subjective sleep quality and perceived physical health were assessed in a large representative sample of 14,179 participants (52.7% females; age range 18-85) from the German Socio-Economic Panel Study across 4 yearly measurement time points. Results: Subjective sleep quality linearly declined from young adulthood until age 60. After age 60 a transient increase in subjective sleep quality occurred that coincides with retirement. Physical health prospectively predicted subjective sleep quality and vice versa. These relations were similar for participants above and below age 60. Discussion: Around retirement a transient increase in subjective sleep quality occurs, which may reflect a decrease in work related distress or an increase in flexibility to organize the day according to one's circadian preferences. Perceived physical health is important for subjective sleep quality in old adults, but not more important than at younger age.
Keywords: 330; Sleep quality; Physical health; Old age; Retirement; German Socio-Economic Panel Study